Ion Kinetics in a Hot Flow Anomaly: MMS Observations. Issue 21 (4th November 2018) - Schwartz, Steven J; Avanov, Levon; Turner, Drew; Zhang, Hui; Gingell, Imogen; Eastwood, Jonathan P; Gershman, Daniel J; Johlander, Andreas; Russell, Christopher T; Burch, James L; Dorelli, John C; Eriksson, Stefan; et al.
Abstract: Hot Flow Anomalies (HFAs) are transients observed at planetary bow shocks, formed by the shock interaction with a convected interplanetary current sheet. The primary interpretation relies on reflected ions channeled upstream along the current sheet. The short duration of HFAs has made direct observations of this process difficult. We employ high resolution measurements by NASA's Magnetospheric Multiscale Mission to probe the ion microphysics within a HFA. Magnetospheric Multiscale Mission data reveal a smoothly varying internal density and pressure, which increase toward the trailing edge of the HFA, sweeping up particles trapped within the current sheet. We find remnants of reflected or other backstreaming ions traveling along the current sheet, but most of these are not fast enough to out‐run the incident current sheet convection. Despite the high level of internal turbulence, incident and backstreaming ions appear to couple gyro‐kinetically in a coherent manner. Plain Language Summary: Shock waves in space are responsible for energizing particles and diverting supersonic flows around planets and other obstacles. Explosive events known as Hot Flow Anomalies (HFAs) arise when a rapid change in the interplanetary magnetic field arrives at the bow shock formed by, for example, the supersonic solar wind plasma flow from the Sun impinging on the Earth's magnetic environment. HFAs are known to produce impacts all the way to ground level, but the physics responsible for their formation occur too rapidly to be resolved by previous satellite missions. This paper employs NASA's fleet of four Magnetospheric Multiscale satellites to reveal for the first time clear, discreet populations of ions that interact coherently to produce the extreme heating and deflection. Key Points: MMS observations reveal distinct ion velocity‐space populations within a Hot Flow Anomaly (HFA) The HFA interior varies smoothly in density with a swept‐up pressure excess toward the trailing edge The HFA interior displays coherent kinematic coupling between antisunward and sunward backstreaming ions